Cover Image, Volume 38, Issue 5. Issue 5 (19th April 2017) - Gallion, Jonathan; Koire, Amanda; Katsonis, Panagiotis; Schoenegge, Anne‐Marie; Bouvier, Michel; Lichtarge, Olivier
Abstract : On the cover : The cover image, by Jonathan Gallion and Amanda Koire et al., is based on the Research Article Predicting phenotype from genotype: Improving accuracy through more robust experimental and computational modeling, Pages 569–580. DOI10.1002/humu.23193